Formononetin ameliorates SP-induced urticaria in mice via suppressing TAK1/MAK signaling pathway - Yan Wu; Chunyu Li (PLoS ONE, 2026)
Background Chronic idiopathic urticaria (CIU) is a condition that significantly impacts patient well-being, requiring effective therapeutic strategies. Formononetin, a natural isoflavone with anti-inflammatory properties, has shown promise in allergic conditions. However, its specific effects and mechanism in CIU are not fully understood. Methods Comparative analyses were conducted between normal and formononetin-treated groups, along with mechanistic investigations into the TAK1/MAPK pathway both in vivo and in vitro . Cell morphology, cytokine secretion, histamine release, and TAK1/MAPK pathway alterations were assessed. Results Formononetin treatment led to a dose-dependent reduction in MC degranulation, histamine release, and secretion of inflammatory cytokines (TNF-α, IL-1β, IL-6). Additionally, formononetin inhibited the phosphorylation of TAK1, p38, ERK1, and JNK similar to a TAK1 inhibitor in murine and cellular models. Conclusion Formononetin shows potential as an anti-allergic agent by alleviating inflammatory responses in CIU through suppression of the TAK1/MAPK pathway in both murine models and MC/9 cells.